Fluorimetric Methods for the Determination of Terazosin HCl in Drug Substance and Dosage Forms: Fingerprinting and Anti-diabetic analysis of alcoholic and aqueous stem extracts B. tomentosa - Taghreed A. Mohamed; Nahla S.Ismail (Iranian Journal of Pharmaceutical Sciences, 2014)
Determination of terazosin hydrochloride dihydrate (TRZ) in drug substance and tablets was studied by fluorimetric techniques. The fluorimetric methods are based on: (1) measurement of the native fluorescence of the drug in water at 750 nm after excitation at 330 nm. (2) sensitizing the native fluorescence by formation a binary complex of drug with aqueous uranyl acetate (0.1% w/v) at the same Ex / Em. under the described condition. the proposed methods were applicable over the concentration range of (10 -1000 and 0.5-12 ng mL-1) with good correlation ((r2=0.9982 and 0.9987), limit of detection of ( 3.47 and 0.198 ng/mL) and a lower limit of quantification of (10.5 and 0.6 ng mL-1) for method (1) and (2), respectively. The described methods were successfully applied for the determination of TRZ in its commercial tablets without interference from common excipients.